Pharmacokinetic variability of factor VIII concentrates in Chinese pediatric patients with moderate or severe hemophilia A - Zhenping Chen; Kun Huang; Gang Li; Yingzi Zhen; Xinyi Wu; Ai Di; Guoqing Liu; Zekun Li; Iorio Alfonso; Runhui Wu (Wiley, 2021)
ABSTRACT Importance The use of factor VIII (FVIII) concentrates under pharmacokinetic (PK) guidance has become the main approach for treatment of hemophilia. However, limited PK research has been conducted in Chinese pediatric patients. Objective To investigate the PK parameters of various FVIII concentrates in Chinese pediatric patients. Methods Seventy‐nine patients were enrolled (28 treated with Kogenate FS®, 23 treated with Advate ®, and 28 treated with GreenMono™). All enrolled patients participated in single‐dose PK analysis after at least a 3‐day washout period. Blood samples were collected predose, as well as at 1 h, 9 h, 24 h, and 48 h after infusion; FVIII levels were measured using a one‐stage clotting assay. von Willebrand Factor Antigen (VWF:Ag) levels and blood types were also determined. PK parameters were evaluated by WAPPS‐Hemo. Results Mean values of terminal elimination half‐life time (t1/2) for the Kogenate FS®, Advate®, and GreenMono™ FVIII groups were 12.24 h, 10.18 h, and 9.62 h; median clearance values were 4.16, 6.23, and 5.11 mL·kg−1·h−1; and median in vivo recovery values were 1.97, 1.55, and 1.61 IU/dL per IU/kg. Longer t1/2, higher in vivo recovery, and lower clearance were observed in patients with higher VWF:Ag level who were treated with recombinant concentrates. Interpretation Chinese pediatric patients with hemophilia had FVIII PK characteristics similar to those previously observed in non‐Chinese children, including large variation among individuals. VWF:Ag level and FVIII brand were associated with differences in FVIII PK. Thus, PK‐guided dosing should be used to optimize individualized therapy in Chinese children.